"LipServants" and Mutes: Experiencing Precarity Through the Commercial Control of Language in Tammy Baikie's Critical Dystopia Selling LipService (2017). Issue 2 (2nd July 2020) - Clarke, Lynne
Abstract : This article notes the relevance of Selling LipService by Tammy Baikie (2017) at the contemporary moment, as it deals with capitalism, consumerism, language, branding, communication and liberty. The novel's dystopian setting reveals characters' precarity caused by the commercial exploitation of language. The article deploys Judith Butler's theories of precarity, amplified by reference to Achille Mbembe's concept of necropolitics. It further reveals the significance of theorists' commentaries on language, branding and critical dystopianism, used as tools to investigate the novel. The article argues that Baikie's critical dystopia highlights challenges to precarity through the original use of language and resistance by disaffected outsiders beyond the system, allowing readers to glimpse hopeful elements of social dreaming in and beyond the text.